Potential Climate Change Mitigation Opportunities in the Transport Sector in Vietnam - RCEE Energy and Environment JSC; Full Advantage Co. Ltd. (World Bank, Washington, DC, 2017)
Vietnam's transport sector plays an important role in its socioeconomic development. Passenger transport helps meets daily needs and contributes significantly to tourist service development while freight transport helps meet the country's demand for delivery of raw materials and of semi-finished products to production facilities and for transport of finished products to consumers. With the overall growth in transport in the country, each of the main forms of transport (road, railway, aviation, inland waterways and maritime) are currently increasing the total fuel use for transport and as a result overall greenhouse gas emissions. In addition to the mix of transport modes used, the major factors affecting the impact of this growth on current and future greenhouse gases from each mode of transport are the quality and quantity of the vehicles and supporting infrastructure and the type of fuels used and their efficiency. The following sections evaluate the infrastructure and fuel use of each of the modes of transport (sections 1.1-1.5), the current and projected greenhouse gas emissions from the sector and the reasons for this (section 2), and typologies of interventions that can reduce the emissions from the sector (section 3).